An updated protocol to assess arm swimming power in front crawl - Dominguez-Castells, R.; Izquierdo, M.; Arellano, R. (International Journal of Sports Medicine, 2013)
Mechanical power output is a reliable predictor of swim speed in front crawl. However, a complete power curve (power vs. load) has not been described for swimming, and intra-cycle power has not been assessed. The purpose of this study was to examine intra-cycle power output at propulsive phases and to determine maximum swimming power, the corresponding load and swimming speed. 18 swimmers (age 22.10±4.31years, height 1.79±0.07 m, arm span 1.85±0.08 m and body mass 76.74±9.00 kg) performed a swim power test. It consisted of 12.5 m all-out swims with only the arms, with a load attached to the swimmer. A linear encoder and a load cell recorded intra-cycle speed and force in each trial. The test was recorded with 2 underwater cameras. Intra-cycle power was obtained for propulsive stroke phases (pull: 60.32±18.87 W; push: 71.21±21.06 W). Peak power was 114.37±33.16 W. Mean maximum swim power was 66.49 W (0.86 W/kg), which was reached at a swimming velocity of 0.75 m/s with a 47.07% of the individual maximal load. Significant positive correlation (r=0.76, p<0.01) between maximum swim power and maximum swim speed was observed. These results suggest that the proposed test may be a training tool that is relatively simple to implement and would provide swimmers and coaches with quick feedback.